Organochlorine pesticide residues in sediment and water from NairobiRiver, Kenya: levels, distribution, and ecological risk assessment - Ndunda, Elizabeth N.; Madadi, Vincent O.; Wandiga, Shem O. (Environmental Science and Pollution Research, 2018)
Production and use of most organochlorine pesticides (OCPs) was banned through the Stockholm Convention on persistentorganic pollutants. However, appreciable amounts are still detected in the environment due to their persistence, illegal use, andreleases from contaminated soils and obsolete stocks. The present study investigated the levels of OCP residues in Nairobi River.Sediment and water samples were collected from three sites along the river and screened for 17 OCPs using gas chromatographyelectron capture detector (GC-ECD). Mean pesticide residues ranged from 0.01 to 41.9μgkg−1in sediment and below detectionlimit to 39.7 ng L−1in water. In sedimentα-HCH,β-HCH,γ-HCH, heptachlor epoxide, andp,p′-DDD were detected in allsamples, whileα-HCH,γ-HCH,δ-HCH, heptachlor epoxide, endosulfan I, and endrin were detected in all water samples. Levelsof OCPs in water were below the WHO maximum allowable limits for surface water. However, values higher than the sedimentquality guidelines for sediment samples in Racecourse Road Bridge and Outering Road Bridge were reported, thus confirmingthe toxicity to aquatic organisms. Consequently, as these compounds are known to bio-accumulate in fatty tissues, continued useof the river water poses a health risk to animals and humans.
Keywords: Nairobi River; Organochlorine pesticides; Persistent organic pollutants; Gas chromatography electron capturedetector; Residues